Foundation and Epistemology of Islamic Education in Indonesia - Tatang Muh Nasir; Gina Aria Sonia; Nasirudin Rusyd; Muhammad Kafnun Kafi; Leti Latifah (Khazanah Pendidikan Islam, 2023)
The aim of the national education system is to establish educational standards that are adopted by Islamic education providers in Indonesia as a whole. This preference of course leaves open the question of how far the educational foundation has been met by national education standards. This descriptive-analytic study explains the foundations of Islamic education as included in national education standards. This study can identify that the foundation of Islamic education is relevant to the educational standards set by the national education system. The national education system has contained human values with various conditions, challenges and changing times which are very quickly eroding human values themselves. The national education system has demonstrated an effort to change humans with knowledge, attitudes and behavior that are in accordance with the framework of Islamic values, because the aim of education is to create Human Resources (HR) who have an Islamic personality, in the sense that their way of thinking is based on Islamic values and has a spirit in accordance with the spirit and breath. Islam. Islamic education based on the Koran and Sunnah is designed by taking into account the concept of Islamization of knowledge regarding the nature of science in an Islamic perspective which is based on spiritual power which has a harmonious relationship between reason and revelation, the interdependence of reason and intuition towards the epistemology of the spiritual values of Islamic education like this. become a beacon of hope in building a better life for Muslims with a more established and stable Islamic civilization. Islamic educational epistemology like this emphasizes the totality of experience and reality (empiricism) and advocates many ways to study nature (rationalism, so that knowledge obtained from revelation and reason from observation and intuition from tradition and theoretical speculation truly produces a balanced generation of intellectual abilities. and spirituality and morality.